Long noncoding RNA Meg3 regulates cardiomyocyte apoptosis in myocardial infarction. Issue 8 (December 2018) - Wu, Hongchun; Zhao, Zhen-Ao; Liu, Junwei; Hao, Kaili; Yu, You; Han, Xinglong; Li, Jingjing; Wang, Yixuan; Lei, Wei; Dong, Nianguo; Shen, Zhenya; Hu, Shijun
Abstract Myocardial infarction (MI), with a major process of cardiomyocyte death, remains a leading cause of morbidity and mortality worldwide. To date, it has been shown that lncRNAs play important roles in cardiovascular pathology. However, the detailed studies on lncRNAs regulating cardiomyocyte death in myocardial infarction are still limited. In this study, we found a progressively upregulated expression ofMeg3 in mouse injured heart after MI. Gain-of-function and loss-of-function approaches further revealed pro-apoptotic functions ofMeg3 in rodent cardiomyocytes. Moreover, Meg3 was directly upregulated by p53 in hypoxic condition, and involved in apoptotic regulation via its direct binding with RNA-binding protein FUS (fused in sarcoma). Afterwards, adult MI mice that underwent intramyocardial injection with adeno-associated virus serotype 9 (AAV9) system carryingMeg3 shRNA showed a significant improvement of cardiac function. Moreover, we also found thatMEG3 was increased in clinical heart failure samples, and had conservatively pro-apoptotic function in human cardiomyocytes that were differentiated from the human embryonic stem cells. Together, these results indicate that p53-inducedMeg3 –FUS complex plays an important role in cardiomyocyte apoptosis post-MI, and its specific knockdown in cardiomyocytes with AAV9 system represents a promising method to treat MI for preclinical investigation.